Hydration assessment of athletes - Cheuvront, S. N.; Sawka, D. M. N. (Sports Science Exchange, 2005)
The purposes of this paper are to: 1) evaluate several common methods for assessing hydration status of athletes, 2) provide acceptable outcome criteria for the most accurate and reliable methods and 3) offer application guidance for athletes and coaches.